2019
DOI: 10.1021/acs.jpcc.9b00422
|View full text |Cite
|
Sign up to set email alerts
|

Why Does the Photoluminescence Efficiency Depend on Excitation Energy in Case of a Quantum Dot? A Case Study of CdSe-Based Core/Alloy Shell/Shell Quantum Dots Employing Ultrafast Pump–Probe Spectroscopy and Single Particle Spectroscopy

Abstract: Core/alloy-shell/shell quantum dots (CASS QDs) have been shown to exhibit excitation energy dependent PL efficiency. The magnitude of the normalized transient population has been shown to increase more than 5-fold with decreasing the excitation energy. For high energy excitation cooling of the exciton (predominantly electron) to band edge is much slower (rise time of ∼526 fs) in comparison to low energy excitation (rise time of <∼100 fs). Time constant associated with the excitation energy dependent dynamics o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

12
129
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(141 citation statements)
references
References 56 publications
12
129
0
Order By: Relevance
“…The PL Eff ( E ) collected for other samples of CdSe QDs contained both minima and decreasing PL efficiencies with increasing excitation energy . These latter EED trends are consistent the results obtained for various QD systems ,, and perovskite NPs. , …”
mentioning
confidence: 87%
“…The PL Eff ( E ) collected for other samples of CdSe QDs contained both minima and decreasing PL efficiencies with increasing excitation energy . These latter EED trends are consistent the results obtained for various QD systems ,, and perovskite NPs. , …”
mentioning
confidence: 87%
“…Similar results have been reported for the CdSe and InP-based QDs. [41][42][43][44][45][46] As can be observed from Fig. 4(i), the ON-OFF events are anti-correlated.…”
Section: R) †)mentioning
confidence: 99%
“…Application of near-unity QY NCs to demonstrating condensed phase laser cooling, however, requires better understanding of how NC QYs are impacted by excitation conditions such as excitation intensity and/or excitation wavelength. The latter is of particular concern given prior studies, suggesting that varying NC excitation energies leads to different emission QYs. Such excitation energy-dependent (EED) emission QYs were first demonstrated by Hoheisel et al who showed through photoluminescence excitation (PLE) measurements that CdSe NC emission QYs decreased monotonically when ensembles were excited to the blue of their band edges. This was rationalized as exciting particles into a continuum of states, distinct from confined NC states.…”
mentioning
confidence: 99%